Discotic liquid crystals 45 years later. Dendronized discs and crowns increase liquid crystal complexity to columnar from spheres, cubic Frank-Kasper, liquid quasicrystals and memory-effect induced columnar-bundles. (December 2022) - Percec, Virgil; Sahoo, Dipankar
Highlights: Classic discotic liquid crystals are self-organized from their supramolecular columns (76/85). Dendronized disc-like molecules self-organize helical columns and spherical helices (75/83). Helical columns self-assembled from supramolecular spherical helices (62/68). Frank-Kasper and liquid quasicrystal liquid crystals (47/52). Complex bundles of helical columns nucleated via supramolecular orientational memory (75/84). Abstract: In 1977 Chandrasekhar laboratory reported the first examples of a new class of thermotropic liquid crystals self-organized from planar disc-like molecules substituted with alkyl groups. X-ray analysis demonstrated that these disc-like molecules stack on top of each other at irregular spacing in columns located in the paraffin melt of their alkyl groups. These supramolecular columns self-organize in a hexagonal array defined as the new thermotropic discotic or columnar hexagonal liquid crystal phase. This new thermotropic liquid crystal phase has translational periodicity in two dimensions and liquid-like disorder in the third one, along the column axis. In 2002 Bushby and Lozman dedicated a brief review article to the 25 anniversary of discotic liquid crystals. This review also included a brief discussion of supramolecular discs and columns self-organized from self-assembling dendrons and dendrimers. The current publication is not another review but a brief perspective on new liquid crystal phases self-organized from dendronized rigid planar and conformationally flexible discs as well as from crown-like molecules. Crown-like molecules are the most stable conformation of a transient unstable disc. All dendronized disc-like and crown molecules adopt a crown conformation that self-assemble helical columns and spherical helices. A large diversity of new liquid crystalline phases self-organize from these helical columns and spherical helices. They include helical columnar hexagonal phases from crowns and from supramolecular spheres, Frank-Kasper A15 (known as cubic phase of space group P m 3 ¯ n ), σ phase (also known as tetragonal of space group P 42 / mnm ), 12-fold quasi liquid crystals (QLC) and supramolecular orientational memory (SOM) derived complex bundles of supramolecular columnar hexagonal arrays that are not yet completely elucidated. The impact of Chandrasekhar on the discovery of self-assembling dendrons and dendrimers via his biaxial nematic liquid crystal concept will also be discussed. This perspective is dedicated to the 45 anniversary of the discovery of discotic liquid crystals and to the memory of Professor Sivaramakrishna Chandrasekhar, a modest, respectful and great scientist. Graphical abstract: Image, graphical abstract